The genomic study of repetitive elements in Solea senegalensis reveals multiple impacts of transposable elements in the evolution and architecture of Pleuronectiformes chromosomes - Cross, Ismael; Rodríguez, María E.; Portela-Bens, Silvia; Merlo, Manuel A.; Gálvez-Salido, Aaron; Navajas-Pérez, Rafael; Rebordinos, Laureana (Frontiers in Marine Science, 2024)
Pleuronectiformes are flatfishes with high commercial value and a prominent example of successful marine adaptation through chromosomal evolution. Hence, the aim of this study was to analyze the 14 relative abundance of repetitive elements (satellite DNA and transposable elements (TE)) in the 15 genome of 10 fish species (8 flatfish) delving into the study of the species of special relevance, 16 Senegalese sole, Solea senegalensis. The results showed differences in the abundance of repetitive elements, with S. senegalensis exhibiting the highest frequency and coverage of these elements reaching the 40% of the genome and not at random distribution. It is noteworthy the presence of relevant peaks of Helitrons in centromeric/pericentromeric positions mainly in the bi-armed chromosomes 1, 2, 4, 6, 7, and 9. The position of the centromeres of this species determined through the genomic localization of the family of satellite DNA PvuII, and other repetitive sequences was obtained de novo. This allowed us to know the genomic position of the centromeres in 19 out of the 21 chromosomes of S. senegalensis. Helitrons showed an accumulation of tandem copies mainly in the pericentromeric positions of chromosomes 1 and 2, occupying a region, in the first case, of 600Kb of tandem repeats. That has only been previously described in mammals and plants. Divergence and copy number studies indicated the presence of active families in the species’ genome and the existence of two important events of transposon activity (burst) in the genome of S. senegalensis, mainly accentuated in Helitrons. The results showed that only the families of DNA transposons exhibited a landscape with symmetrical bell-shaped distribution. The phylogenetic analysis of Helitron families revealed the presence of two large groups of families and the presence of four groups of sequences with heterogeneous distribution among chromosomes. Finally, the phylogenomic analysis of 8615 sequences belonging to Helitron insertions from 5 families of flatfish and two external species, allowed to classify the copies into nine groups of sequences with different levels of divergence and clusters, including some branches with distant phylogenetically species. The implications of this study will help to expand the knowledge of chromosome structure and evolution of these species.